Copper-Doped Carbon Dots for Optical Bioimaging and Photodynamic Therapy - Wang, Jingmin; Xu, Mingsheng; Wang, Dong; Li, Zhenzhen; Primo, Fernando Lucas [UNESP]; Tedesco, Antonio Claudio; Bi, Hong (American Chemical Society (ACS), 2019)
Carbon dots (CDs), as an effective bioimaging agent, have aroused widespread interest. With the increasing number of CDs used in photodynamic therapy (PDT), developing efficient CDs with multiple functions such as imaging and phototherapy has become a new challenge. Herein, a new type of copper-doped CDs (Cu-CDs) with a high fluorescence quantum yield of 24.4% was synthesized from a copper complex of poly(acrylic acid) through coordination between the carboxyl group and copper ions. Owing to their good solubility, bright fluorescence, and low cytotoxicity, the Cu-CDs can be used for fluorescence imaging in both the HeLa (human cervical cancer) cell line and SH-SY5Y (human neuroblastoma cells) multicellular spheroids (3D MCs). More importantly, the Cu-CDs show a high quantum yield of singlet oxygen (1O2; 36%), good photoinduced cytotoxicity, and effective inhibition of 3D MC growth. Therefore, the Cu-CDs can be used as a promising imaging-guided PDT agent. This study provides a new carbon-based nanomaterial for multifunctional photodiagnostic and therapeutic agents for biological applications.